Case Report: A Novel Mutation Identified in CHST14 Gene in a Fetus With Structural Abnormalities - Zhou, Yuan-Yuan; Du, Yu-Fang; Lu, Qing; Zhai, Xiu-Zhang; Shi, Ming-Fang; Chen, Dan-Yun; Liu, Sun-Rong; Zhong, Ying (Frontiers in Genetics, 2022)
Background: Musculocontractural Ehlers–Danlos syndrome (mcEDS) is a rare heritable connective tissue disease with various symptoms. The diagnosis of mcEDS is difficult because of the large overlap of clinical symptoms between different EDS subtypes. Methods: We performed karyotype analysis, gene copy number variation detection, whole-exome sequencing, and Sanger sequencing to reveal the underlying genetic etiology of a fetus with structural abnormalities in feet and kidneys. Results: A likely pathogenic mutation [NM_130468.3 c.958C>T (p.Arg320*)] and an uncertain significance mutation [NM_130468.3 c.896A>G (p.Tyr299Cys)] were identified in the carbohydrate sulfotransferase 14 (CHST14) gene by whole-exome sequencing and validated by Sanger sequencing. Conclusion: The two identified mutations appear highly likely to be the genetic causes of the fetal structural abnormalities.